La post-mémoire et le problème de l’identité nationale et individuelle présentés dans la littérature mauricienne contemporaine d’expression française - Szkonter-Bochniak, Anna (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In the article the author analyses the influence of post-memory in the formationof national and individual identity among the inhabitants of the young Republic of Mauritiuspresented in contemporary Mauritian literature in French. Important and at the sametime tragic historical events of Mauritius are: slavery, the arrival and labour of indenturedworkers from India and the tragedy of the Chagos Islanders. The author analyses sometexts by Ananda Devi and Shenaz Patel in which both writers describe the impact of ancestralhistory on the lives of characters representing the next generation from different ethnicgroups living on the island. In her analysis, the author refers to the works of MarianneHirsch, Paul Ricoeur and Alex Mucchielli.